Prevalence of work-related musculoskeletal disorders in agricultural farmers of Bhaktapur District, Nepal - Mahto, Prakash Kumar; Bhupal Gautam, B.P.T. (International Journal of Occupational Safety and Health, 2018)
Background: Work-related musculoskeletal disorders are present in a range of occupations. This is confirmed from a number of studies done around the world. However, few attempts have been done to document the presence of musculoskeletal disorders in occupational diseases in Nepal and there are hardly any studies done to see musculoskeletal disorders in farmers of Nepal. Nepal is an agricultural country and traditional practices in farming are adopted demanding a lot on the manual work. Objectives: Aim of this study is to find out the prevalence of musculoskeletal disorders in Bhaktapur district of Nepal. Methods: This is a descriptive cross-sectional study design. A convenience sample of 246 farmers from Bhaktapur district, Nepal aged between 24-65 years, were included in the study. The Nordic musculoskeletal questionnaire was a tool adapted to measure MSDs in the farmers. Descriptive analysis of data was done. Results: Farmers (n=246) reported pain in all the nine areas of the body mentioned in the questionnaire. More than 70% of farmers have some kind of musculoskeletal disorders. However, six major areas of pain were identified as: Neck-31(12.6 %), Shoulder-26(10.6%), Elbow- 30(12.2%), Low back- 89(36.2%), Knee- 53(21.5%) and ankle 32(13%). Conclusion: The prevalence of musculoskeletal disorders in farmers is very high. Lack of awareness about the MSDs and improper knowledge of ergonomics causes the problems.